HUSH WOMAN! THE COMPLEX ‘DISABLED’ WOMAN IN NIGERIA’S LEGAL AND HUMAN RIGHTS FRAMEWORK: A DECONSTRUCTION (African Disability Rights Yearbook, 2021)
Few studies have paid enough attention to the relationship that exists between law and the oppression that women in Nigeria face, mainly when this oppression manifests as sexism and disability discrimination simultaneously. The interest has mostly been on the oppression that manifests as sexism and disability discrimination as separate issues. Yet, reality shows that many women in Nigeria have sustained injuries as a result of sexist oppression and have become disabled. This situation is testament to the interactions and intersections that exist between identity categories of sex/gender and disability as well as resultant oppression of sexism and disability discrimination. However, these interactions are rarely acknowledged. Against this backdrop, the objective of this article is to ask the question: Who is a disabled woman in Nigeria? By asking the question, the intention is to expose the Nigerian legal framework's definition of the disabled woman as 'born and essentialist'. Yet, unlike the essentialist approach that law and human rights adopt, I demonstrate, how the identity categories of womanhood and disability that a disabled woman embodies are unstable and fluid. Unfortunately, Nigeria's legal and human rights framework hardly contemplates this fluidity and instability. I posit in the conclusion that particularly where it concerns women, Nigeria's legal and human rights framework can no longer afford to define violations of rights as if disability and sex/gender are entirely separate, stable, monolithic and essentialist identity categories.
Keywords: Nigeria; law; oppression; sexism; disability discrimination; legal and human rights framework